2019
DOI: 10.3892/ol.2019.10901
|View full text |Cite
|
Sign up to set email alerts
|

Chemovirotherapy for pancreatic cancer: Gemcitabine plus oncolytic measles vaccine virus

Abstract: Oncolytic virotherapy with vaccine viruses employs replicative vectors, which quite selectively infect tumor cells leading to massive virus replication followed by subsequent profound tumor cell death (oncolysis). Measles vaccine virus (MeV) has already shown great oncolytic activity against different types of cancers, including pancreatic cancer. Gemcitabine is a first line chemotherapeutic drug used for pancreatic cancer in palliative treatment plans. Furthermore, this drug can be used to induce senescence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Synergistic effects of oncolytic MeV and radiotherapy against glioblastoma were observed in vitro and in a xenograft model [ 48 ]. In vitro studies have also demonstrated successful combination of oncolytic MeV with chemotherapies such as paclitaxel [ 49 ], camptothecin [ 50 ], and gemcitabine [ 51 ]. Combination with the anti-epidermal growth factor receptor (EGFR) monoclonal antibody nimotuzumab was reported to result in increased antitumor efficacy in laryngeal cancer models [ 52 ].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Synergistic effects of oncolytic MeV and radiotherapy against glioblastoma were observed in vitro and in a xenograft model [ 48 ]. In vitro studies have also demonstrated successful combination of oncolytic MeV with chemotherapies such as paclitaxel [ 49 ], camptothecin [ 50 ], and gemcitabine [ 51 ]. Combination with the anti-epidermal growth factor receptor (EGFR) monoclonal antibody nimotuzumab was reported to result in increased antitumor efficacy in laryngeal cancer models [ 52 ].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Thus, infection with MV has been reported to accelerate the lysis of a panel of cancer cell lines induced into senescence after treatment with chemotherapeutic drugs [ 140 ]. The combinatorial effect of measles-based virotherapy, together with the chemotherapeutic agent that induces senescence, gemcitabine, on human pancreatic cancer cell lines, has also been evaluated [ 141 ]. The authors found that the combination was significantly more effective than the individual treatments reducing cell viability.…”
Section: Virus and Senescencementioning
confidence: 99%
“…The chemovirotherapeutic combination of gemcitabine plus oncolytic MeV resulted in improved tumor reduction in vitro (hPDAC cell lines) [157].…”
Section: Mevmentioning
confidence: 99%